Bifurcation of limit cycles by perturbing piecewise non-Hamiltonian systems with nonlinear switching manifold. (February 2021) - Ramirez, O.; Alves, A.M.
Abstract: This paper is devoted to the study of limit cycles that can bifurcate of a perturbation of piecewise non-Hamiltonian systems with nonlinear switching manifold. We derive the first order Melnikov function to these systems. As application, the sharp upper bound of the number of bifurcated limit cycles of two concrete systems, whose switching manifolds are algebraic curves, is presented.